Exam Ref AZ-900 Microsoft Azure fundamentals - Cheshire, Jim (Microsoft Press : Pearson Education, 2019)
Prepare for Microsoft Exam AZ-900-and help demonstrate your real-world mastery of cloud services and how they can be provided with Microsoft Azure. Designed for professionals in any non-technical or technical role, Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified Fundamentals level. Focus on the expertise measured by these objectives: Understand cloud concepts Understand core Azure services Understand security, privacy, compliance, and trust Understand Azure pricing and support This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you want to show foundational knowledge of cloud services and their delivery with Microsoft Azure; no technical background or IT experience is required About the Exam Exam AZ-900 focuses on knowledge needed to evaluate cloud service's value; explain IaaS, PaaS, and SaaS; compare public, private, and hybrid cloud models; understand core Azure architectural components, products, and management tools; describe the Azure Marketplace, its usage, and key solutions; understand Azure security, identity services, and monitoring; manage privacy, compliance, and data protection; price subscriptions and manage costs; choose support options; use Service Level Agreements; and understand the Azure service lifecycle. About Microsoft Certification Passing this exam fulfills your requirements for the Microsoft Certified Azure Fundamentals credential, demonstrating that you understand cloud concepts, core Azure Services, Azure pricing and support, and the fundamentals of cloud security, privacy, compliance, and trust. See full details at: www.microsoft.com/learn.